A Review of Clinical Guidelines for Physical therapy Management in patients with Heart Failure - Salman Latif, Saleh Shah, Muhammad Naveed Babur, Ali Sufyan, Saira Farooqui, Mariam Javaid, Muhammad Sharyar, Sania Akram (Cuestiones de Fisioterapia, 2025)
The global health challenge posed by heart failure (HF) is substantial, affecting millions of individuals and putting considerable pressure on health systems worldwide. HF is characterized by the heart's failure to pump enough blood to the body's tissues, with debilitating symptoms, poor quality of life, and frequent visits to the hospital. HF was previously published as a report by the 2022 AHA/ACC/HFSA Joint Committee on Clinical Practice Guidelines, and continues to bean important contributor to global morbidity and mortality statistics, of which effective management is a pivotal part(1).Physical therapy (PT) has become one of the keystones in the holistic approach to the treatment of HF, particularly in terms of improving functional capacity, quality of life, and decreasing readmission rates. Clinical guidelines have strongly encouraged the incorporation of structured exercise programs, inspiratory muscle training, and patients’ education as part of HF care(2).Nevertheless, low awareness among providers and non-adherence among patients have been barriers to the use of these interventions in the clinical setting